Internet of Things: an evolution of development and research area topics - Oliveira e Sá, Jorge (2017)
Internet of Things (IoT) is a hot topic in the Europe Union (EU). In the year of 2015 the EU established an Alliance of Internet of Things Innovation (AIOTI) and this alliance included the IoT European Research Cluster (IERC) on the Internet of Things in the work group 01. IERC was established in 2007 and addresses the large potential for Internet of Things-based capabilities in Europe and to coordinate the convergence of ongoing activities. This organization regularly publishes Strategic Research Agendas with short, medium and long term forecasts of development and research topics. The aim of this paper is to study these Strategic Research Agendas published in the years 2010, 2011, 2012, 2014 and 2016 and make an identification of topics, in order to understand its evolution over time in terms of areas that have already been researched (or the research has already started) as well as those not yet explored. This work was performed based on a literature review methodology to identify the evolution in all the Strategic Research Agendas published in the years of 2010, 2011, 2012, 2014 and 2016.